2015
DOI: 10.1051/0004-6361/201425040
|View full text |Cite
|
Sign up to set email alerts
|

Frontier Fields: Combining HST, VLT, andSpitzerdata to explore thez~ 8 Universe behind the lensing cluster MACSJ0416.1−2403

Abstract: Context. The Hubble Space Telescope (HST) Frontier Fields (HFFs) project started at the end of 2013 with the aim of providing extremely deep images of six massive galaxy clusters. One of the main goals of this program is to push several telescopes to their limits to provide the best current view of the earliest stages of the Universe. The analysis of the initial data has already demonstrated the huge capabilities of the program. Aims. We present a detailed analysis of z ∼ 8 objects behind the HFFs lensing clus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
58
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 77 publications
10
58
1
Order By: Relevance
“…4, which indicates a good consistency with respect to previous estimates. A similar result is found by making a comparison with the much smaller LBG samples from the M0416 fields (Laporte et al 2015;Coe et al 2015;McLeod et al 2015) and from the A2744 parallel field (Ishigaki et al 2015;McLeod et al 2015). We inspected the 16 LBGs missing from our A2744 cluster catalogue and found that in three cases they are undetected, while 13 are very close to bright galaxies and are not deblended from them.…”
Section: Comparison With Previous Worksupporting
confidence: 71%
“…4, which indicates a good consistency with respect to previous estimates. A similar result is found by making a comparison with the much smaller LBG samples from the M0416 fields (Laporte et al 2015;Coe et al 2015;McLeod et al 2015) and from the A2744 parallel field (Ishigaki et al 2015;McLeod et al 2015). We inspected the 16 LBGs missing from our A2744 cluster catalogue and found that in three cases they are undetected, while 13 are very close to bright galaxies and are not deblended from them.…”
Section: Comparison With Previous Worksupporting
confidence: 71%
“…The full Spitzer Frontier Fields observations are complete and were publicly released in early 2016. The first Frontier Fields observations have already probed galaxies during the epoch of reionization to intrinsic luminosities fainter than any previously seen (e.g., Zitrin et al 2014;Atek et al 2015;Laporte 2015;Livermore et al 2017) and improved our statistical accounting of z>8 galaxies (e.g., Kawamata et al 2015;McLeod et al 2015McLeod et al , 2016Ishigaki et al 2016). The full data set will place strong statistical constraints on the faint end of the luminosity function during this era (Robertson et al 2015).…”
mentioning
confidence: 91%
“…Moreover, the program offers a crucial test for our current capabilities of data analysis, from the perspective of the new, large amount of data that will come from future facilities like the James Webb Space Telescope. Published works on FF data include McLeod et al (2015), Wang et al (2015), Oesch et al (2015), Laporte et al (2015), Atek et al (2015).…”
Section: Introductionmentioning
confidence: 99%